1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Finding the tangent line using implicit differentiation.

  1. Nov 16, 2012 #1
    1. The problem statement, all variables and given/known data

    The equations ##2x^3y+yx^2+t^2=0##, ##x+6+t-1=0## implicitly define a curve $$f(t) = \begin{pmatrix} x(t)\\y(t) \end{pmatrix}$$ that satisfies ##f(1)=\begin{pmatrix} -1\\1 \end{pmatrix}.##

    Find the tangent line to the curve when ##t=1##.

    2. Relevant equations

    The chain rule to find the derivative of f would give something like: $$\frac {df}{dt} = \frac {\partial f}{\partial x}\frac {\partial x}{\partial t} + \frac {\partial f}{\partial y}\frac {\partial y}{\partial t}.$$

    And the equation of the tangent plane should be given by the formula: $$f(t_0)+\frac {df}{dt}(t_0) \cdot (t-t_0).$$

    3. The attempt at a solution

    Differentiating both sides of each equation with respect to ##t## gives $$2x^3\frac {dy}{dt}+6x^2y\frac {dx}{dt}+2xy\frac {dx}{dt} +x^2\frac {dy}{dt} + 2t = 0$$$$\frac {dx}{dt}+\frac {dy}{dt}+1=0$$Solving for ##\frac {dx}{dt}## and ##\frac {dy}{dt}## when ##t=1## and ##f(1)=(-1,1)## gives $$\frac {dx}{dt} =-3/5$$$$\frac {dy}{dt}=-2/5.$$
     
    Last edited: Nov 16, 2012
  2. jcsd
  3. Nov 16, 2012 #2

    ehild

    User Avatar
    Homework Helper
    Gold Member

    You need the equation of the tangent line. How can you write it in terms of x and y?

    ehild
     
  4. Nov 16, 2012 #3
    ##f(x_0,y_0)+\nabla f(x,y)\cdot (x-x_0,y-y_0)?##
     
  5. Nov 16, 2012 #4

    ehild

    User Avatar
    Homework Helper
    Gold Member

    The curve is in the x,y plane and the tangent line is a straight line of form (y-yo)=a(x-xo). You need that tangent line. The slope of the line is a=dy/dx, you get it with implicit differentiation.

    ehild
     
  6. Nov 16, 2012 #5
    ##f(t)## defines ##x## and ##y## implicitly as functions ##x=x(t)## and ##y=y(t)##. To get ##\frac {dy}{dx}##, would I need to define ##y## implicitly as a function ##y=y(x)##?
     
  7. Nov 16, 2012 #6

    ehild

    User Avatar
    Homework Helper
    Gold Member

    Are you sure that you copied the problem correctly?
    X(1)≠-1, as -1+6+1-1 =5 .
    Is not the second equation x+y+t-1=0?

    ehild
     
  8. Nov 16, 2012 #7

    ehild

    User Avatar
    Homework Helper
    Gold Member

    No, you can get dy/dx as (dy/dt)/(dx/dt). That is implicit differentiation.

    ehild
     
  9. Nov 16, 2012 #8
    Then, ##\frac {dy}{dx}=\frac {2}{3}##. And substituting the values for ##y-y_0=a(x-x_0)## gives $$y-1=\frac {2}{3}(x+1).$$
     
    Last edited: Nov 16, 2012
  10. Nov 16, 2012 #9

    ehild

    User Avatar
    Homework Helper
    Gold Member

    Looks good.

    ehild
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook